#1**+5 **

We have a rule here that helps on this one......

log a - log b = log(a/b) Note that the bases * have* to be the same!!

So we have

log_{3} 54 - log_{3} 2 = log_{3} (54/2) = log_{3} 27

And remember, we're just asking, "What power do we put on 3 to raise 3 to 27??"

The answer is.........3 !!!!

CPhill Jul 9, 2014

#1**+5 **

Best Answer

We have a rule here that helps on this one......

log a - log b = log(a/b) Note that the bases * have* to be the same!!

So we have

log_{3} 54 - log_{3} 2 = log_{3} (54/2) = log_{3} 27

And remember, we're just asking, "What power do we put on 3 to raise 3 to 27??"

The answer is.........3 !!!!

CPhill Jul 9, 2014